1995
DOI: 10.1289/ehp.95103162
|View full text |Cite
|
Sign up to set email alerts
|

Contaminant-related suppression of delayed-type hypersensitivity and antibody responses in harbor seals fed herring from the Baltic Sea.

Abstract: Recent mass mortalities among several marine mammal populations have led to speculation about increased susceptibility to viral infections as a result of contaminant-induced immunosuppression. In a 2.5-year study, we fed herring from either the relatively uncontaminated Atlantic Ocean or the contaminated Baltic Sea to two groups of captive harbor seals and monitored immune function in the seals. Seals fed the contaminated fish were less able to mount a specific immunological response to ovalbumin, as measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
85
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(88 citation statements)
references
References 37 publications
3
85
0
Order By: Relevance
“…Our findings are (34) consistent with the results of several marine mammal studies. Harbor seals fed HAHcontaminated herring from the Baltic Sea had reduced delayed-type hypersensitivity (T-cell-mediated) and reduced mitogeninduced proliferative T-cell responses (67,68). Mitogen-induced proliferative Tcell responses were inversely correlated with blood PCB and DDE concentrations in male bottlenose dolphins from the west SagB coast of Florida (69).…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings are (34) consistent with the results of several marine mammal studies. Harbor seals fed HAHcontaminated herring from the Baltic Sea had reduced delayed-type hypersensitivity (T-cell-mediated) and reduced mitogeninduced proliferative T-cell responses (67,68). Mitogen-induced proliferative Tcell responses were inversely correlated with blood PCB and DDE concentrations in male bottlenose dolphins from the west SagB coast of Florida (69).…”
Section: )mentioning
confidence: 99%
“…In herring gull eggs, gradiSagB ents in PCBs and DDE all occurred in the (15) same rank order. However, PCBs occurred at much higher concentrations than DDE, and suppression of T-cell-mediated (68), but mitogen-induced proliferation of B cells was not affected (10) (67). B-cell proliferation showed no associations with organochlorines in male bottlenose dolphins from the west coast of Florida (69).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…There was an inverse relationship between DTH swelling and total Ah receptorbinding contaminant levels. Furthermore, the serum antibody titers to ovalbumin were approximately 37% lower in the seals fed the contaminated herring than those fed the control herring (51). Earlier studies had shown that seals fed PCB-contaminated fish had significantly lower serum retinol levels, which when converted to vitamin A, can play an important role in resistance to microbial infections (52,53).…”
Section: Immunosuppression In Marine Mammalsmentioning
confidence: 95%
“…reproductive toxicity (Helle et al 1976a;Helle et al 1976b;Reijnders, 1986), hormonal alterations (Brouwer et al 1989;Subramanian et al 1987), and immunotoxicity (De Swart et al 1994;De Swart et al 1995b;Ross et al 1995a;Ross et al 1995b). Recent morbillivirus related mass mortalities among marine mammals inhabiting polluted coastal waters De Swart et al 1995a) led to speculation about a possible contribution of environmental contaminant-induced immunosuppression to the severity and extent of these epizootics (Osterhaus and Vedder, 1989;Simmonds and Johnston, 1989).…”
Section: Introductionmentioning
confidence: 99%